2005
DOI: 10.1590/s0102-695x2005000400004
|View full text |Cite
|
Sign up to set email alerts
|

Cissampelos sympodialis Eichl. (Menispermaceae) inhibits anaphylactic shock reaction in murine allergic model

Abstract: The murine model of OVA-induced immediate allergic reaction was used to evaluate the effectiveness of intraperitoneal sub-acute treatment with the leaf hydroalcoholic extract of Cissampelos sympodialis (AFL) in the anaphylactic shock reaction, IgE production and the background proliferative response. BALB/c mice treated with AFL ranging from 200 to 400 mg/kg/day for 5 days before and during OVA-sensitization strongly reduced the animal death and promoted reduction in total and OVA-specifi c serum IgE level. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
2
5
0
1
Order By: Relevance
“…The warifteine-treatment reduced these responses. These results corroborate with previously data [32,33] that showed that the C. sympodialis extract also inhibited the IgE production and anaphylactic shock reaction in OVA-sensitized BALB/c mice adding support to the interpretation that the alkaloid possesses anti-allergic properties.…”
Section: Discussionsupporting
confidence: 92%
“…The warifteine-treatment reduced these responses. These results corroborate with previously data [32,33] that showed that the C. sympodialis extract also inhibited the IgE production and anaphylactic shock reaction in OVA-sensitized BALB/c mice adding support to the interpretation that the alkaloid possesses anti-allergic properties.…”
Section: Discussionsupporting
confidence: 92%
“…These findings, together with previous reports of this plant and warifteine inhibiting anaphylactic shock reaction in OVA sensitized mice, allergic pleurisy and pulmonary inflammation; suggest their therapeutic potential as anti-allergic and anti-asthmatic [9,26,10]. This alkaloid also reduced mast cell degranulation and hyperalgesia response in rats [12].…”
Section: Discussionsupporting
confidence: 70%
“…However, the same treatment was not able to inhibit the anaphylactic shock induced by compound 48/80. These data show that the effect of the extract is dependent on mechanisms involving IgE production (Bezerra-Santos et al, 2005).…”
Section: Activity Of Cissampelos Sympodialis In Anaphylactic Shock Rementioning
confidence: 74%